Establishment of the Art Market in the Context of Ukrainian Historical and Cultural Tradition - Rusakov, Serhii (Studia Warmińskie, 2022)
The origins of the art market in Ukraine are analyzed on the basis of the life of artists, art exhibitions, art salons and creative circles of the 17th - early 20th centuries. The author researches the socio-cultural processes of different periods of Ukrainian culture that influenced the phenomenon of the art market, in particular its educational and commercial aspects. The peculiarity of the art market in Ukraine is connected with the popularization of young Ukrainian artists, the creation of favorable conditions for the realization of their talent, the unification of artistic forces from different Ukrainian regions and on. The art market is considered as a value-semantic space, where works of art are circulated, thanks to which new ideas emerge in the Ukrainian cultural space. The author uses the cultural-historical method, which allows to analyze, describe and generalize the patterns of origin, formation and development of the art market as an important component of socio-cultural evolution of Ukrainian culture. The important role of patronage, which contributed to the development of the Ukrainian art market, is considered. The origin and development of art exhibitions, which gained popularity in the 19th century, despite the long-standing tradition of exhibition activities in Ukraine, are studied. Mobile art exhibitions became a unique phenomenon, which determined the main trend in the fine arts of the last third of the 19th century. The activities of the Taras Shevchenko Scientific Society, which contributed to the creation of a portrait gallery – the largest project related to the fine arts, headed by M. Hrushevsky – are reviewed separately. The author emphasizes that the activities of progressive Ukrainian of art contributed to the creation of many artistic associations, which played an important role in promoting the works of Ukrainian artists, awakening public interest in art.